PENGOLAHAN LIMBAH PERTANIAN MENJADI AMONIASI JERAMI DALAM MENINGKATKAN EKONOMI MASYARAKAT DI KELURAHAN BUNGUS BARAT KECAMATANA BUNGUS TELUK KABUNG KOTA PADANG - Fridarti fridarti; Syafrizal Syafrizal; Devi Dianti; Nazaruddin Nazaruddin; Erwin Erwin; Syaifuddin Islami; Sri Mulyani; Zulkarnaini Zulkarnaini (Jurnal Hilirisasi IPTEKS, 2024)
This community service activity takes the form of clinical coaching on agricultural waste management in raising goats/cattle which aims to transfer knowledge and improve skills regarding the management of agricultural waste processing such as rice straw as an alternative feed ingredient and the rice straw ammonization process. This activity also aims to increase public knowledge about management of the maintenance and processing of agricultural waste in the form of ammoniated rice straw, so that it can overcome difficulties in procuring animal feed. The method used in the coaching clinic is guidance on waste management using science and technology as well as practice or demonstration of making straw ammonia. This activity was carried out through several stages, namely socialization & coaching clinic about goat/cattle farming, animal feed ingredients and making straw ammonization. This activity received a very positive and enthusiastic response from members and succeeded in providing an understanding of solutions to feed difficulties in the dry season. Apart from that, the ammoniated rice straw that had been produced was tried to be given to livestock and the results were very clearly liked by cattle. This shows that ammoniated straw is preferred by cattle because the nutritional content of rice straw that has been processed using the ammonia process can be used as an alternative feed. The raw material for rice straw is easy to obtain in West Bungus Village, Teluk Kabung Subdistrict, so that every farmer can carry out rice straw ammonia processing using simple technology with optimal results. Rice straw that has been processed can reduce production costs so that it will improve the community's economy